Cardiac MOLLI T1 mapping at 3.0 T: comparison of patient-adaptive dual-source RF and conventional RF transmission - Rasper, Michael; Nadjiri, Jonathan; Straeter, Alexandra S.; Settles, Marcus; Laugwitz, Karl-Ludwig; Rummeny, Ernst J.; Huber, Armin M. (International Journal of Cardiovascular Imaging, 2017)
To prospectively compare image quality and myocardial T1 relaxation times of modified Look-Locker inversion recovery (MOLLI) imaging at 3.0 T (T) acquired with patient-adaptive dual-source (DS) and conventional single-source (SS) radiofrequency (RF) transmission. Pre- and post-contrast MOLLI T1 mapping using SS and DS was acquired in 27 patients. Patient wise and segment wise analysis of T1 times was performed. The correlation of DS MOLLI measurements with a reference spin echo sequence was analysed in phantom experiments. DS MOLLI imaging reduced T1 standard deviation in 14 out of 16 myocardial segments (87.5%). Significant reduction of T1 variance could be obtained in 7 segments (43.8%). DS significantly reduced myocardial T1 variance in 16 out of 25 patients (64.0%). With conventional RF transmission, dielectric shading artefacts occurred in six patients causing diagnostic uncertainty. No according artefacts were found on DS images. DS image findings were in accordance with conventional T1 mapping and late gadolinium enhancement (LGE) imaging. Phantom experiments demonstrated good correlation of myocardial T1 time between DS MOLLI and spin echo imaging. Dual-source RF transmission enhances myocardial T1 homogeneity in MOLLI imaging at 3.0 T. The reduction of signal inhomogeneities and artefacts due to dielectric shading is likely to enhance diagnostic confidence.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 3 T; Cardiac T; Dual-source RF transmission; MOLLI; RF shimming